2003
DOI: 10.1083/jcb.200209014
|View full text |Cite
|
Sign up to set email alerts
|

Elevated glucose inhibits VEGF-A–mediated endocardial cushion formation

Abstract: Atrioventricular (AV) septal defects resulting from aberrant endocardial cushion (EC) formation are observed at increased rates in infants of diabetic mothers. EC formation occurs via an epithelial-mesenchymal transformation (EMT), involving transformation of endocardial cells into mesenchymal cells, migration, and invasion into extracellular matrix. Here, we report that elevated glucose inhibits EMT by reducing myocardial vascular endothelial growth factor A (VEGF-A). This effect is reversed with exogenous re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 53 publications
4
79
0
Order By: Relevance
“…Thus, MMP2 clearly has the potential to modulate an important stage of cardiac morphogenesis-the interval when endocardial endothelial cells transform and invade the cardiac jelly ECM (Song et al, 2000). In fact, murine endocardial epithelial-to-mesenchymal transformation is positively correlated with levels of MMP2 expression (Enciso et al, 2003). The expression patterns in Figures 2 and 3 suggest that MMP2 is not required for the transformation event itself, but rather, for mesenchymal cell invasion.…”
Section: Mmp2 Is Active During Endocardial Mesenchyme Invasionmentioning
confidence: 70%
“…Thus, MMP2 clearly has the potential to modulate an important stage of cardiac morphogenesis-the interval when endocardial endothelial cells transform and invade the cardiac jelly ECM (Song et al, 2000). In fact, murine endocardial epithelial-to-mesenchymal transformation is positively correlated with levels of MMP2 expression (Enciso et al, 2003). The expression patterns in Figures 2 and 3 suggest that MMP2 is not required for the transformation event itself, but rather, for mesenchymal cell invasion.…”
Section: Mmp2 Is Active During Endocardial Mesenchyme Invasionmentioning
confidence: 70%
“…New studies show that myocardial VEGF expression is repressed in the nascent cushion and that this allows endocardial endothelial cells to initiate their differentiation into mesenchymal cells (Chang et al, 2004). The role of VEGF in EMT is likely to be complex, and depend on spatial and temporal regulation given that, in two other studies of mouse embryonic valve development, VEGF was found to be a positive regulator of EMT (Enciso et al, 2003;Hallaq et al, 2004). In our laboratory, we showed a functional link between VEGF and the transcription factor NFATc1 in human post-natal valve endothelial cells (HPVEC) (Johnson et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Serial sections through the entire AV cushion were examined and the section with the most positive cells was used for quantitation. Atrio-ventricular canal endocardial cushion explant culture Atrio-ventricular (AV) explant cultures were performed as described (Enciso et al, 2003). Briefly, the AV canal and ventricle (AV explant) from E10.5 mice with >28 somites were placed on rat tail type I collagen (Fisher, Collaborative Biomedical) gels which were hydrated for a minimum of 1 hour with 100 µl of Medium 199 supplemented with 1% FBS, 100 u/ml penicillin, 100 µg/ml streptomycin, and 0.1% each of insulin, transferrin, and selenium (GIBCO BRL).…”
Section: Immunohistochemistrymentioning
confidence: 99%